2021
DOI: 10.1109/jeds.2020.3040445
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Trap and Recovery Characteristics Based on Low-Frequency Noise for E-Mode GaN HEMTs Under Electrostatic Discharge Stress

Abstract: The ESD effects on the E-mode AlGaN/GaN high-electron mobility transistors (HEMTs) with p-GaN gate are investigated under repetitive TLP pulses. Firstly, the degradation and recovery of output, transfer characteristics, gate-leakage characteristics and low-frequency noises (LFN) are analyzed in detail before and after reverse electrostatic discharge (ESD) stress. The experimental results show that the electrical characteristics of the devices gradually degraded as the transmission line pulse (TLP) pules increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…However, both extractions of N t show the highest values in Device C. Device C with a p-GaN gate layer demonstrates a trap density in the range of 1.5 × 10 19 -2.7 × 10 19 cm −3 eV −1 which is about one order of magnitude larger than devices without a p-GaN gate layer under different drain current similar to the others published AlGaN/GaN HEMT devices [18,19]. The possible cause is supposedly due to Mg out-diffusion from the p-GaN layer into the AlGaN barrier layer or GaN channel layer [20,21]. Meanwhile, the measured N t values vary with input gate overdrive voltages indicating the Fermi level changes at the AlGaN/GaN interface [13].…”
Section: Lfn Measurement and Analysissupporting
confidence: 70%
“…However, both extractions of N t show the highest values in Device C. Device C with a p-GaN gate layer demonstrates a trap density in the range of 1.5 × 10 19 -2.7 × 10 19 cm −3 eV −1 which is about one order of magnitude larger than devices without a p-GaN gate layer under different drain current similar to the others published AlGaN/GaN HEMT devices [18,19]. The possible cause is supposedly due to Mg out-diffusion from the p-GaN layer into the AlGaN barrier layer or GaN channel layer [20,21]. Meanwhile, the measured N t values vary with input gate overdrive voltages indicating the Fermi level changes at the AlGaN/GaN interface [13].…”
Section: Lfn Measurement and Analysissupporting
confidence: 70%
“…This is strong evidence that the flicker noise is dominated by the number fluctuations (Δ N ) mechanism, [ 11 ] which has been frequently found in GaN‐based D‐mode HEMT [ 12,13 ] and (nonregrowth) E‐mode HEMT. [ 14 ] In this Δ N case, explained by the McWhorter model, [ 15 ] the 1/ f noise is induced by the fluctuations of the interfacial charge, resulting from trapping/detrapping processes of free electrons in border traps close to the channel interface. Therefore, the normalized drain current can be described in proportion to the transconductance g m throughSidIds2=SVfb(gmIds)2where S Vfb is the input‐referred voltage noise PSD at flat‐band voltage and is a constant factor.…”
Section: Resultsmentioning
confidence: 99%
“…However, owing to the lack of discharge path in the gate electrode of the p-GaN HEMTs, the devices exhibit poor ESD robustness in the gate-to-source condition, with an equivalent V HBM of only 0.2~0.33 kV. E. Canato [15] and Yiqiang Chen [16,17] reported the gate-tosource ESD failure and degradation mechanisms of p-GaN HEMTs, which mainly rely on the trapping effect and device geometry. To improve the gate-to-source ESD robustness for the p-GaN HEMT, Xin et al reported a unidirectional AlGaN/GaN ESD protection diode based on a self-triggered discharging channel [14].…”
Section: Introductionmentioning
confidence: 99%